Investigating the development of masculine identities in physical education. Issue 6 (23rd July 2020) - Stewart, Sean; Gray, Shirley; Kelly, John; MacIsaac, Sarah
ABSTRACT: This research examines the masculine identities and experiences of males within the subject of PE. Specifically, it examines the masculine identities of two groups of boys in the Scottish secondary physical education (PE) context: Secondary 1 (S1: age 12–13) and Secondary 4 (S4: age 15–16). Drawing from Hegemonic Masculinity Theory and Inclusive Masculinity Theory, this research set out to explore how masculine identities co-exist and develop within the same context, building on previous research that has examined masculine identities in the Scottish PE context. To do so, guided by key principles of ethnography and using qualitative methods, S1 and S4 boys were observed in their PE lessons for a period of 3 months. In the third month, four pupils in each class volunteered to take part in semi-structured group interviews. The results from our thematic analysis indicated that both groups performed different masculine identities. The S1 boys that were observed and interviewed adopted inclusive masculinities, where they seemed able to display a range of gendered behaviours without fear of stigmatisation or marginalisation. Conversely, the majority of the S4 boys observed and all of the boys that were interviewed embodied an exclusive form of masculinity, using their bodies to allow them to enact a range of masculine behaviours while maintaining their superior position in the social hierarchy. This article highlights the need for more research into the construction of masculine identities as pupils navigate PE and school. We also suggest that teachers can be more pro-active in maintaining broad, inclusive and critical conceptions of PE as pupils progress from the junior to the senior years.